The effect of an even-pacing strategy on exercise tolerance in well-trained cyclists - Thomas, K.; Stone, M.; Gibson, A. S.; Thompson, K.; Ansley, L. (European Journal of Applied Physiology, 2013)
Purpose Previous research has suggested that the optimal pacing strategy for self-paced exercise lasting >4 min is a uniform distribution of work, but this posit is not well established for prolonged endurance events. This study examined the utility of even pacing during 20 km cycling time trials (TTs). Methods Fifteen well-trained male cyclists ( VO2max = 4.80 ± 0.38 L/min) completed three best effort self-paced (SP) simulated 20 km TTs, followed by two even-paced trials. In one even-paced trial, participants cycled to exhaustion (EPtlim) at a fixed intensity equivalent to their best SP performance. In the other EP trial, participants were instructed to maintain this target intensity for a distance of 20 km, but the actual intensity was free to vary depending on the effort and cadence of the cyclist (EP-maintained). Cardiorespiratory, blood lactate and perceptual (RPE and affect) measures were assessed throughout. Results Nine out of fifteen cyclists failed the EPtlim task, completing 51-83 % (10.3-15.3 km) of the work done in their SP trial. Failure as a result of even pacing was associated with a faster rise in blood lactate, attainment of a higher relative intensity during SP and a moderate fast starting strategy. This failure was independent of the nature of the even-paced task. Conclusion By adopting an uneven, parabolic distribution of work, cyclists in this study were able to achieve an average intensity during self-paced exercise in excess of their maximum sustainable power output. A subsequent matched even-paced bout resulted in cumulative metabolic stress that could not be managed by moment-to-moment changes in power output. These results challenge the notion that strict even pacing is optimal for endurance time trial events.